2002
DOI: 10.1097/00005373-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Safety and Accuracy of Physical Examination in the Evaluation of Knee Dislocation for Injury of the Popliteal Artery: A Prospective Study

Abstract: This limited series suggests that the presence or absence of an injury of the popliteal artery after knee dislocation can be safely and reliably predicted, with a 94.3% positive predictive value and 100% negative predictive value. Arteriography appears to be unnecessary when physical examination is negative but may avert negative vascular exploration when physical examination is positive. This approach substantially reduces cost and resource use without adverse impact on the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 16 publications
0
55
0
8
Order By: Relevance
“…Sillanpää et al [21] similarly warned increasing body proportions are leading to a changing paradigm in the epidemiology of knee dislocations and associated vascular injuries. Although historical literature suggested that mechanism of injury and the degree of injury severity (ISS) were useful predictors of vascular injury [7,8,10,14,25], this was not the case in our study or others [3,21]. To our knowledge, our study is one of the only studies that investigates open injury as a risk factor for vascular injury after knee dislocation; however, Wright et al [27] reported a series of 19 patients with open knee dislocations and found that nine (47%) had some form of concomitant vascular injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sillanpää et al [21] similarly warned increasing body proportions are leading to a changing paradigm in the epidemiology of knee dislocations and associated vascular injuries. Although historical literature suggested that mechanism of injury and the degree of injury severity (ISS) were useful predictors of vascular injury [7,8,10,14,25], this was not the case in our study or others [3,21]. To our knowledge, our study is one of the only studies that investigates open injury as a risk factor for vascular injury after knee dislocation; however, Wright et al [27] reported a series of 19 patients with open knee dislocations and found that nine (47%) had some form of concomitant vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…A similar concept is used by acute care surgeons during the evaluation of appendicitis, where it has been suggested that a significant false positive rate is necessary to ensure a diagnostic sensitivity of 100% [5]. The absence of pulses alone has been suggested in some studies [7,8,10,11,14,24,25] as being sufficient to detect vascular injury, although each of the studies had limited patient sample size and relied on antiquated technology. Moreover, these studies were limited by their selective use of the ABI, which has been shown to be a valuable adjunct to the vascular examination.…”
Section: Discussionmentioning
confidence: 99%
“…If basic physical examination reveals intact peripheral pulses, an arteriography is not necessary. On the other hand, a suspicious peripheral perfusion status should lead to an arteriography at an early stage [13].…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies [27,28] (Fig. 11) where patients were managed with modern reconstruction techniques, and evaluated using the IKDC [55] score, no patients were rated as normal at the time of review. Overall, 38 % were nearly normal, 40 % were abnormal and 21 % were severely abnormal.…”
Section: Outcome Of Knee Dislocationmentioning
confidence: 99%